Recovery methods for athletes during high-intensity training - Yang, M.; Meng, D.; Mejarito, C. L. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: The continuous improvement of the level of modern sports competition compels continuous reform and constant updates on sports training theory; sports training research is migrating from continuous low-intensity to high-intensity interval, and many studies have shown that high-intensity interval training has a good effect on athletes. Objective: Investigate the effect of different recovery modalities during high-intensity interval training on the athletic performance of young male runners. Methods: Using body morphological index measurement, high-intensity intermittent exhaustion test, and statistical analysis, forty young male long-distance runners from sports schools were randomly divided into active recovery group (AR, n=20) and passive recovery group (PR, n=20), maximal oxygen uptake (VO2max) and maximal aerobic speed (MAV) were measured by incremental load exercise test, and interval exercise capacity and time to exhaustion (ET) were recorded. Results: Compared with pre-training, MAV and ET in both groups increased significantly after training (P<0.05); there was no significant difference in MAV on RA group after training (P>0.05). Conclusion: High-intensity interval training with active recovery can significantly improve athletic ability and performance in young male runners in the long term.